PEMBERDAYAAN KELUARGA DALAM PENGEMBANGAN TERNAK PUYUH DI DESA PEKIK NYARING KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Rita, Wismalinda; Herizon, Catur; P, Definiati (P-2776-3072)
Quails breeding is easy to cultivate, can produce in a relatively short time and does not require a prominent location. Besides, male quail and rejected livestock are very well sold in the market. The obstacle to the development of quail so far is the high cost of concentrate feed with prices that tend to fluctuate so that the nutritional needs of quail have not been fulfilled, which in turn has an impact on production. Knowledge and skills of quail breeders are required in the management of quail rearing. Selection of seeds, feeding with good nutrition by utilizing feed ingredients from local sources is the right solution. This activity aims to increase knowledge of the PKK (group of women in the village) to develop quail farms. Activities are carried out in the form of program socialization and counseling. As a result, the activity has run smoothly; women of the PKK Pekik Nyaring can understand the management of quail breeding, especially the selection of seeds and the provision of quality feed with good nutrition.